Substituting x with π/2 - x gives the equivalent integral,
![\displaystyle\int_0^(\frac\pi2)\log(\tan(x))\,\mathrm dx=-\int_(\frac\pi2)^0\log(\cot(x))(-\mathrm dx)=\int_0^(\frac\pi2)\log(\cot(x))\,\mathrm dx](https://img.qammunity.org/2021/formulas/mathematics/college/yg7uzerw3jrrvz6jbswqsb3qv8kag05zm8.png)
So if we let J denote the value of the integral, we have
![J=\displaystyle\int_0^(\frac\pi2)\log(\tan (x))\,\mathrm dx](https://img.qammunity.org/2021/formulas/mathematics/college/8mo92nn6p325ewllasbnt5kzcdqj8va13s.png)
![J=\displaystyle\int_0^(\frac\pi2)\log(\cot (x))\,\mathrm dx](https://img.qammunity.org/2021/formulas/mathematics/college/1znhpfhzdxa3hl3zznp0fbdnp8kiok4x01.png)
![\implies 2J=\displaystyle\int_0^(\frac\pi2)\left(\log(\tan (x))+\log(\cot (x))\right)\,\mathrm dx](https://img.qammunity.org/2021/formulas/mathematics/college/lpigfmhmuqe5tu6097bouwtri1ddmxabfj.png)
Condensing the logarithms, we have
log(tan(x)) + log(cot(x)) = log(tan(x) cot(x)) = log(1) = 0
since cot(x) = 1/tan(x), which means
![2J=\displaystyle\int_0^(\frac\pi2)0\,\mathrm dx=0](https://img.qammunity.org/2021/formulas/mathematics/college/wm0t6g9zna2yuwjpguffopjxyoropba16k.png)
and so the original integral has a value of J = 0.